(untitled) (Web of Teachers: Inderscience Research, 2025)
This article highlights the importance of digital transformation in the human resources management system in the context of globalization and the need for its phased planning. The article examines the possibilities of optimizing personnel management through modern technologies, artificial intelligence, cloud computing and analytical systems. It also provides recommendations for the formation of an HR strategy based on priority areas such as improving the skills of the workforce through digital transformation, establishing remote work, and automating work processes. The problems that arise in the process of digital transformation, ways to solve them, and mechanisms that serve to increase efficiency are also analyzed.